Vitamin C Content and Antioxidant Activities in Chicken Nuggets with Additions Brokoli and Purple Cabbage - Qorry Aina; Alvia Nur Layli; Yenny Putri Arisandy (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to determine the content of vitamin C and antioxidant activity in chicken nuggets added with broccoli and purple cabbage through organoleptic testing. This type of research is a quasi experiment with a complete randomized design with 4 types of treatment namely B1K1 = 15% : 15%, B1K2 = 15% : 30%, B2K1 = 30% : 15%, B2K2 = 30% : 30%. Organoleptic test data collection techniques using a questionnaire on 28 panelists rather trained nutritional undergraduate students STIKES Surabaya. Vitamin C content test was carried out by spectrophotometry method and antioxidant activity by DPPH method in the best treatment of chicken nugget products and control 3 repetitions. Kruskal Wallis test results showed significant values ​​of color (p = 0.117), aroma (p = 0.039), taste (p = 0.028), texture (p = 0.169), preference level (p = 0.043) while the results of paired t-test showed significant value of vitamin C content (p = 0,000) and antioxidant activity (p = 0,000). The best treatment of chicken nuggets is B1K1 chicken nuggets. The results of the average content of vitamin C control chicken nuggets of 1.472 mg / 100gr lower than the B1K1 chicken nugget of 9,805 mg / 100gr. The average result of antioxidant activity of control chicken nuggets was 27.06% lower than B1K1 chicken nuggets of 54.96%. The conclusion of this study is the content of vitamin C and antioxidant activity in nuggets with the addition of broccoli and purple cabbage with nuggets without the addition of different broccoli and purple cabbage.